2007
DOI: 10.1063/1.2747216
|View full text |Cite
|
Sign up to set email alerts
|

Structural, morphological, and optical properties of AlGaN/GaN heterostructures with AlN buffer and interlayer

Abstract: Alx Ga1-x NGaN (x∼0.3) heterostructures with and without a high-temperature (HT) AlN interlayer (IL) have been grown on sapphire (Al2 O3) substrates and AlN buffer/ Al2 O3 templates by metal organic chemical vapor deposition. The effects of an AlN buffer layer (BL) grown on an Al2 O3 substrate and an AlN IL grown under the AlGaN ternary layer (TL) on structural, morphological, and optical properties of the heterostructures have been investigated by high-resolution x-ray diffraction, spectroscopic ellipsometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 36 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…Therefore, GaN and some other compounds have been studied extensively for their applications in short wavelength optical and high-power/temperature devices, such as light emitting diodes (LEDs), laser diodes (LDs), metal-semiconductor (MS) Schottky barrier diodes (SBDs), metal-insulator-semiconductor high-electron-mobility transistors (MISHEMTs). GaN high-electron-mobility transistors (HEMTs) with Schottky/rectifier metal contact have demonstrated excellent highfrequency, high-power, high temperature and recently good microwave-noise characteristics [1][2][3][4][5][6][7][8][9][10]. The performance level of GaN/ AlGaN HEMT devices has increased rapidly over the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GaN and some other compounds have been studied extensively for their applications in short wavelength optical and high-power/temperature devices, such as light emitting diodes (LEDs), laser diodes (LDs), metal-semiconductor (MS) Schottky barrier diodes (SBDs), metal-insulator-semiconductor high-electron-mobility transistors (MISHEMTs). GaN high-electron-mobility transistors (HEMTs) with Schottky/rectifier metal contact have demonstrated excellent highfrequency, high-power, high temperature and recently good microwave-noise characteristics [1][2][3][4][5][6][7][8][9][10]. The performance level of GaN/ AlGaN HEMT devices has increased rapidly over the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure.5 Chen and co-workers reported that In vacancy islands on the surface of the samples or ordered vacancy rows caused lateral segregation [22]. The surface roughness of the samples may be attributed to In segregation and white rust [23]. White rust can be seen on the surface of both samples in AFM images.…”
Section: Afmmentioning
confidence: 84%
“…[1][2][3][4] Due to lack of native GaN substrates, heteroepitaxy raises a challenge for the good structural quality, which is a must for device applications, but there are ways to achieve it by molecular beam epitaxy and metalorganic chemical vapor deposition. [5][6][7][8][9][10] However, sapphire (Al 2 O 3 ) is used as a substrate for growth of III-N based epitaxial layer in spite of its larger lattice mismatch and larger thermal expansion coefficient by taking diverse growth approaches. 11,12 Notably, in these devices, AlGaN alloys are used as barrier layers, leading to excellent carrier confinement at AlGaN/GaN interface without intentional doping.…”
Section: Introductionmentioning
confidence: 99%